Stressors, coping, and support mechanisms for student athletes combining elite sport and tertiary education: Implications for practice - Cosh, S.; Tully, P. J. (The Sport Psychologist, 2015)
Participation in elite-sport and education is stressful and can result in sacrificed educational attainment. A dearth of research, however, has explored the specific stressors encountered by student athletes and coping strategies used, resulting in limited knowledge of how to best support student athletes. Interviews with 20 Australian university student athletes were conducted and data were analyzed via thematic analysis. Interviewees reported encountering numerous stressors, especially relating to schedule clashes, fatigue, financial pressure, and inflexibility of coaches. Athletes identified few coping strategies but reported that support from parents and coaches was paramount. Athletes would benefit from upskilling in several areas such as effective use of time, self-care, time management, enhanced self-efficacy, and specific strategies for coping with stress. Coaches have the opportunity to play a pivotal role in facilitating successful integration of sport and education.